Mindfulness training as a tool to enhance psychological resilience and speed decision-making in badminton referees - Karim, Taha Yousef; Hassan, Ahmed Sami; Abdulrahman, Mustafa Adnan; Hassan, Marwan Abdulnabi; Mohammed, Ahmed Khalil (Universitas Tanjungpura, 2025)
Background and Study Aim. Competitive sport referees, in most cases, usually are cognitively demanding, and this can lead to their inability to focus, cope with their own feelings, and make good decisions. In badminton, where quick decision-making is inevitable, refereeing requires psychological resilience as well as quick decision-making. The objective of this research was to investigate the impact of a mindfulness-based training program on psychological resilience and decision-making speed among badminton referees in Iraq. Material and Methods. A quasi-experimental design with a pre-post design was used by the researcher on a sample of thirty referees of different refereeing levels, who were divided into two groups (experimental and control). Purposive sampling technique was utilized to obtain a sample of 30 referees. The experimental subjects underwent a mindfulness intervention of eight weeks, 24 sessions with conscious breathing, body scan, reflective pauses, and mental rehearsing of refereeing scenarios. The CD-RISC (Connor–Davidson Resilience Scale) and computerized decision-making speed measure were the assessment tools employed. Results. Statistical analysis showed significant gains in the experimental group over the control group in psychological resilience and decision-making speed, both with large effect sizes. The results show that mindfulness training is helpful for referees to stay calm and think properly during extreme stress. Conclusions. The current research makes a conclusion that adding mindfulness training to the training programs of referees effectively helps to develop mental skills in referees. The study adds to the scarce literature available on applying mindfulness to sports refereeing by providing an evidence-based model that can be used in many diverse.